On Reverie: Using Clinical Facts while Conducting My Group. (September 2017) - Levin, Uri
Reverie, like love, is difficult to define yet easy to acknowledge when present. Like the container and the contained—reverie refers more to a state of mind, to a process, than to a concrete, momentary entity. Bion centralized this concept in the heart of the psychoanalytic discourse, and Ogden gave the term a more practical application. Foulkes had no explicit reference to the concept, yet we might suppose that his 'free floating discussion' is one example of his implicit interest with the idea of reverie experiences in the group. This article will introduce the concept of reverie and its implementations in both individual and group settings. A detailed clinical vignette of my group-analytic group will be presented and discussed, demonstrating how I (sometimes manage to) work with clinical facts in my room.